Engineered bacterial hydrophobic oligopeptide repeats in a synthetic yeast prion, [REP-PSI+] - Gasset-Rosa, Fátima; Giraldo, Rafael (Frontiers in Microbiology, 2015)
The yeast translation termination factor Sup35p, by aggregating as the [PSI+] prion, enables ribosomes to read-through stop codons, thus expanding the diversity of the Saccharomyces cerevisiae proteome. Yeast prions are functional amyloids that replicate by templating their conformation on native protein molecules, then assembling as large aggregates and fibers. Prions propagate epigenetically from mother to daughter cells by fragmentation of such assemblies. In the N-terminal prion-forming domain, Sup35p has glutamine/asparagine-rich oligopeptide repeats (OPRs), which enable propagation through chaperone-elicited shearing. We have engineered chimeras by replacing the polar OPRs in Sup35p by up to five repeats of a hydrophobic amyloidogenic sequence from the synthetic bacterial prionoid RepA-WH1. The resulting hybrid, [REP-PSI+], i) was functional in a stop codon read-through assay in S. cerevisiae; ii) generates weak phenotypic variants upon both its expression or transformation into [psi-] cells; iii) these variants correlated with high molecular weight aggregates resistant to SDS during electrophoresis; and iv) according to fluorescence microscopy, the fusion of the prion domains from the engineered chimeras to the reporter protein mCherry generated perivacuolar aggregate foci in yeast cells. All these are signatures of bona fide yeast prions. As assessed through biophysical approaches, the chimeras assembled as oligomers rather than as the fibers characteristic of [PSI+]. These results suggest that it is the balance between polar and hydrophobic residues in OPRs what determines prion conformational dynamics. In addition, our findings illustrate the feasibility of enabling new propagation traits in yeast prions by engineering OPRs with heterologous amyloidogenic sequence repeats.